Superalloys: An Introduction With Thermal Analysis - Raza, S. S. (University of Eloued جامعة الوادي, 2015)
Solidification studies of Alloy 718, Allvac 718plus and Waspaloy have been of great interest in the present study. Alloy 718 is a precipitation strengthened nickel-iron based alloy. Waspaloy, another precipitation strengthened nickel base superalloy, has a very good strength at temperatures up to ~750 °C whereas Allvac 718Plus is a newly developed nickel based precipitation strengthened superalloy which retains good mechanical properties at up to ~700 °C.These three alloys were investigated in terms of how their respective solidification process reveals upon cooling. Latent heat of solidification has been estimated for all three alloys.Differential thermal analyses (DTA) have been used to approach the task. It was seen that Waspaloy has the smallest solidification range whereas Allvac 718Plus has the largest solidification interval in comparison.
Articale in Journal of fundamental and Applied Sciences Vol. 07, N. 03
Keywords: Superalloys; Phase reactions; Differential Thermal Analysis; Latent heat of Solidification; Solidification interval.